British government information and propaganda, 1939-2009. - Great Britain. Central Office of Information; Great Britain. Ministry of Information; British Library (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2022)
Scanned from source at the British Library, this collection contains a carefully curated selection of materials produced by the British Ministry of Information (MOI) and Central Office of Information (COI) during the period 1939-2009. The items are diverse in nature, ranging from posters and stickers to pamphlets and guidance booklets. The subject matter is just as varied, covering public health, education, social security, civil defence, international politics, race relations, sex discrimination, public sector career opportunities, policing, the environment, and Britain’s membership of the European Economic Community. Most of the items were published during the post-war period, but some date from the First and Second World Wars.
Date range: 1939-2009.
Keywords: Great Britain -- History -- 20th century -- Sources; Great Britain -- Politics and government -- 20th century